Analyzing the Synergistic Response of Soil Nematode Community Structure and Metabolic Footprint to the Southward Migration of Tea in the Qinba Mountain Area - Song, Xinkun (Scientific Journal of Technology, 2025)
As a strategy for adjusting the layout of the agricultural industry, the relocation of tea from the south to the north is gradually unfolding in the Qinba Mountain area. Soil nematodes, as important indicator organisms in soil ecosystems, have a sensitive community structure and metabolic footprint to changes in soil ecological environment during the process of southward tea migration. This article comprehensively elaborates on the structural characteristics and metabolic footprint of soil nematode communities in the Qinba Mountain area, and deeply analyzes their synergistic changes during the process of southward tea northward migration. The aim is to provide theoretical basis for understanding the impact of southward tea northward migration on soil ecosystems and sustainable agricultural development.